2017
DOI: 10.4306/pi.2017.14.6.713
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Traditional Culture and the Interpersonal Psychological Theory on Suicide Research in Korea

Abstract: Korea has the highest suicide rate amongst the OECD countries. Yet, its research on suicidal behaviors has been primitive. While the Interpersonal Psychological Theory of Suicide has gained global attention, there has only been a few researches, which examined its applicability in Korea. In this article, we review the previous studies on suicide and examine the association between the Interpersonal Psychological Theory of Suicide and traditional Korean culture, with an emphasis on Collectivism and Confucianism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In addition, other studies on Latina adolescents in the United States indicated cultural differences in the meaning attributed to PB, where PB could refer to the world being a burden them (Gulbas, Szlyk, & Zayas, 2019). Some studies also discussed the cultural influence on how SRB may be a matter of TB and PB differently in collectivist and non‐Western societies (Hjelmeland & Loa Knizek, 2020; Park, Baik, Kim, & Lee, 2017). Nonetheless, more studies are needed concerning the cultural variation in the meaning of TB and PB, especially when they occur in the collectivist cultures (Gulbas et al, 2019; Schiemer, 2017), including Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies on Latina adolescents in the United States indicated cultural differences in the meaning attributed to PB, where PB could refer to the world being a burden them (Gulbas, Szlyk, & Zayas, 2019). Some studies also discussed the cultural influence on how SRB may be a matter of TB and PB differently in collectivist and non‐Western societies (Hjelmeland & Loa Knizek, 2020; Park, Baik, Kim, & Lee, 2017). Nonetheless, more studies are needed concerning the cultural variation in the meaning of TB and PB, especially when they occur in the collectivist cultures (Gulbas et al, 2019; Schiemer, 2017), including Iran.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been several cross-sectional studies using the data from the "Post-management Service for Suicide Attempters in the Emergency Room" project (25)(26)(27)(28)(29), but few longitudinal studies have been conducted on the effectiveness of postmanagement services for suicide attempters. Results from the current study show that young people used more painkillers for suicide attempts and had more unplanned attempts than planned ones as compared to the adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, experiencing parental verbal or physical abuse will intensify the ideation of suicide in Korean adolescents. 49 Confucianism is another characteristic feature of the Korean culture. Within the family, this likely translates to the boundless and excessive expectations from parents, which children must fulfil.…”
Section: Recommendations For Current Suicide Prevention Strategiesmentioning
confidence: 99%
“…Such an academic stress, also called ‘education fever’ within the family, is one of the causes of suicide in Korean adolescents. 49 In addition, owing to the Korean cultural and social stigma, it is shameful to admit having mental health problems. 27 Thus, family-based programmes to educate parents not to put undue pressure on their children and to improve parents’ mental health literacy and family support, especially in those families with a history of mental illnesses, are indispensable in suicide prevention in the young.…”
Section: Recommendations For Current Suicide Prevention Strategiesmentioning
confidence: 99%